Shareholder Activism - Goranova, Maria; Ryan, Lori Verstegen (Journal of Management, 2014)
Shareholder activism has become a dynamic institutional force, and its associated, rapidly increasing body of scholarly literature affects numerous disciplines within the organization science academy. In addition to equivocal results concerning the impact of shareholder activism on corporate outcomes, the separation of prior research into financial and social activism has left unanswered questions critical for both the scholarly discourse on shareholder activism and the normative debate on shareholder empowerment. The heterogeneity of factors in shareholder activism, such as the firm, activist, and environmental characteristics that promote or inhibit activism, along with the breadth of activism’s issues, methods, and processes, provide a plethora of theoretical and methodological opportunities and challenges for activism researchers. Our multidisciplinary review incorporates the financial and social activism streams and explores shareholder activism heterogeneity and controversy, seeking to provide an impetus for more cohesive conceptual and empirical work in the field.